Clinical and genetic characteristics of craniosynostosis in Hungary. (20th August 2015) - Bessenyei, Beáta; Nagy, Andrea; Szakszon, Katalin; Mokánszki, Attila; Balogh, Erzsébet; Ujfalusi, Anikó; Tihanyi, Mariann; Novák, László; Bognár, László; Oláh, Éva
Abstract : Craniosynostosis, the premature closure of cranial sutures, is a common craniofacial disorder with heterogeneous etiology and appearance. The purpose of this study was to investigate the clinical and molecular characteristics of craniosynostoses in Hungary, including the classification of patients and the genetic analysis of the syndromic forms. Between 2006 and 2012, 200 patients with craniosynostosis were studied. Classification was based on the suture(s) involved and the associated clinical features. In syndromic cases, genetic analyses, including mutational screening of the hotspot regions of the FGFR1, FGFR2, FGFR3, and TWIST1 genes, karyotyping and FISH study of TWIST1, were performed. The majority (88%) of all patients with craniosynostosis were nonsyndromic. The sagittal suture was most commonly involved, followed by the coronal, metopic, and lambdoid sutures. Male, twin gestation, and very low birth weight were risk factors for craniosynostosis. Syndromic craniosynostosis was detected in 24 patients. In 17 of these patients, Apert, Crouzon, Pfeiffer, Muenke, or Saethre–Chotzen syndromes were identified. In one patient, multiple‐suture craniosynostosis was associated with achondroplasia. Clinical signs were not typical for any particular syndrome in six patients. Genetic abnormalities were detected in 18 syndromic patients and in 8 relatives. In addition to 10 different, known mutations in FGFR1, FGFR2 or FGFR3, one novel missense mutation, c.528C>G(p.Ser176Arg), was detected in the TWIST1 gene of a patient with Saethre–Chotzen syndrome. Our results indicate that detailed clinical assessment is of paramount importance in the classification of patients and allows indication of targeted molecular testing with the highest possible diagnostic yield. © 2015 Wiley Periodicals, Inc.